In the eye of the beholder : what six nineteenth-century women tell us about Indigenous authority and identity - Dawson, Barbara (Barbara Chambers) (Open Access e-Books, 2014)
This book offers a fresh perspective in the debate on settler perceptions of Indigenous Australians. It draws together a suite of little known colonial women (apart from Eliza Fraser) and investigates their writings for what they reveal about their attitudes to, views on and beliefs about Aboriginal people, as presented in their published works. The way that reader expectations and publishers requirements slanted their representations forms part of this analysis. All six women write of their first-hand experiences on Australian frontiers of settlement. The division into adventurers (Eliza Fraser, Eliza Davies and Emily Cowl) and longer-term settlers (Katherine Kirkland, Mary McConnel and Rose Scott Cowen) allows interrogation into the differing representations between those with a transitory knowledge of Indigenous people and those who had a close and more permanent relationship with Indigenous women, even encompassing individual friendship. More pertinently, the book strives to reveal the aspects, largely overlooked in colonial narratives, of Indigenous agency, authority and individuality.